1992
DOI: 10.3109/07357909209032772
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dibutyryl Cyclic Adenosine 3',5'-Monophosphate on Morphological Features and Biological Markers of Human Salivary Myoepithelial Cell Line in Culture

Abstract: We have found the emergence of myoepithelial cells (HSG-AZA1) in neoplastic human salivary intercalated duct cell line HSG in culture after treatment with 5-azacytidine. When HSG-ZAZ1 cells were cultured in the presence of N6,O2-dibutyryl cyclic adenosine 3',5'-monophosphate (dB-cAMP), they formed long cytoplasmic processes which were densely packed with ample microfibrils in addition to microtubule bundles. The expression of neuron-specific enolase, synaptophysin, and catecholamine as well as neurofilaments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…9 C6 cells quickly change their morphology when db-cAMP is added, as previously reported for other glioma and blastoma cells. [10][11][12] Prior to introduction of db-cAMP, they exhibit glial (fibroblastic) morphology characterized by elongated stoma with two or more processes. After db-cAMP addition, they become spherical with thin neurites.…”
Section: Resultsmentioning
confidence: 99%
“…9 C6 cells quickly change their morphology when db-cAMP is added, as previously reported for other glioma and blastoma cells. [10][11][12] Prior to introduction of db-cAMP, they exhibit glial (fibroblastic) morphology characterized by elongated stoma with two or more processes. After db-cAMP addition, they become spherical with thin neurites.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that salivary gland tumors consist of several tumor cell components, such as myoepithelial-like tumor cells, duct-like tumor cells, acinus-like tumor cells, epidermoid-like tumor cells, mucin-producing tumor cells and tumor cells with mesenchymal differentiation (17). There are several reports concerning the direction of differentiation in salivary gland tumors or the tumor stem cells of salivary gland tumors (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Sato et al established a cultured salivary gland tumor cell line, HSG (21) and investigated the differentiation potentials of HSG cells (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports concerning the direction of differentiation in salivary gland tumors or the tumor stem cells of salivary gland tumors (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Sato et al established a cultured salivary gland tumor cell line, HSG (21) and investigated the differentiation potentials of HSG cells (22)(23)(24)(25)(26). They reported that HSG cells maintained a phenotype with salivary intercalated duct cells, and could differentiate into several cell types, such as myoepithelial-like cells (22), acinus-like cells (22), squamous cell-like cells (23), chondrocyte-like cells (24), neuronal cell-like cells (25) and osteoblast-like cells (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations